Psychiatric genetic essentialism and stigma in child custody proceedings: public views. Issue 2 (26th August 2021) - Sabatello, Maya; Chao, Audrey; Insel, Beverly J; Corbeil, Thomas; Link, Bruce G; Appelbaum, Paul S
Abstract: The introduction of behavioral, including psychiatric, genetic information in American courts has gained traction but raises concerns of undue influence on judicial outcomes. We conducted a vignette-based survey of a nationally representative sample of US adults to assess how evidence about a parent's psychiatric genetic makeup and explicit and implicit stigmatizing beliefs about psychiatric conditions may affect key decisions in child custody proceedings. Psychiatric genetic evidence did not affect public perspectives on custody decisions, but it increased the genetic essentialist understanding of psychiatric conditions (regardless of a diagnosis). Explicit stigma was associated with a preference to deny parents with a (or with an alleged) psychiatric condition joint custody. Our newly created Implicit Association Test identified an association between psychiatric conditions and perceived bad parenting. Research to identify effective interventions and educational programs to address genetic essentialism and to reduce bias against people, including parents, with psychiatric conditions is urgently needed.